Integralisasi Budaya Dalam Sistem Pendidikan Nasional - Usman Ilyas; Wa Ode Murima La Ode Alumu (Foramadiahi: Jurnal Kajian Pendidikan dan Keislaman, 2019)
In principle direction development culture, is to improve the quality of life of human dan community, heirship culture past to keep important and meaningful, having values new and held interpretation new creativity; sert leads to wholeness view, to stem the appearance of a split and contradiction in the society that pluralistic this. Element cultural must be brought into national education policy which is, the principle of view of life; elementary operation of the activities of educating, determination curriculum (a charge local), motivation learning and living and anvil development more advance